Suppressed GABAergic signaling in the zona incerta causes neuropathic pain in a thoracic hemisection spinal cord injury rat model. (6th October 2016) - Moon, Hyeong Cheol; Lee, Youn Joo; Cho, Chul Bum; Park, Young Seok
Highlights: To test whether GABAergic signals influence SCI-induced neuropathic pain. The author recorded and compared in vivo single-unit, neuronal activity between hemisection-SCI and sham-treated rat models. To test whether muscimol or bicuculline influence neuronal activity in hemisection SCI rat model. Abstract: Objective: Suppression of the gamma -aminobutyric acid (GABA)ergic activity of the zona incerta (ZI) reportedly plays a role in neuropathic pain after spinal cord injury (SCI). A reduction in GABAergic signaling in the ZI of a thoracic hemisection-SCI rat model has been suggested, but not clearly demonstrated. Accordingly, our objective was to investigate whether GABAergic signals influence SCI-induced neuropathic pain. Methods: In vivo, we recorded and compared single-unit, neuronal activity between hemisection-SCI and sham-operated rat models. Furthermore, we analyzed neuronal activity in both models following treatment with either a GABAA receptor agonist (muscimol) or antagonist (bicuculline). Results: Rats that underwent hemisection SCI exhibited reduced hindpaw withdrawal thresholds, latencies, and decreased ZI neuronal activity compared with sham-operated controls. Importantly, muscimol treatment increased, whereas bicuculline decreased, the firing rates of the ZI neurons. The muscimol treated, hemisection-SCI rats also exhibited increased hindpaw withdrawal thresholds and latencies. Conclusions: These data provide evidence that neuropathic pain after SCI is caused by decreased GABAergic signaling in the ZI. Furthermore, our data demonstrate that infusion of a GABAergic drug into the ZI could restore its inhibitory action and improve neuropathic pain behaviors.